Analisis Penerapan SAK-ETAP pada CV Belaban Mekar di Kabupaten Melawi - Diana Octavia Jaiman; Reni Dwi Widyastuti; Endang Kristiawati (Program Studi Akuntansi Universitas Panca Bhakti, 2026)
This study aims to analyze the implementation of accounting practices at CV Belaban Mekar, a company engaged in oil palm seedling cultivation, and to assess its compliance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The main problem identified is the lack of proper recording and preparation of financial statements. Therefore, the researcher reconstructed the financial statements in accordance with applicable standards. The conclusion of this study indicates that the accounting practices at CV Belaban Mekar are not in accordance with SAK ETAP, thus improvements are needed in the recording system and preparation of financial statements to produce more accurate and useful information for decision-making.